Counter modification of hypereutectic gray cast iron - L. Z. Pisarenko (Литьë и металлургия)
Possibility of use of complex modification of hypereutectic gray cast iron by graphitizing and antigraphitizing additions for manufacture of castings with high antifriction and antiscratching properties is shown.